MICRO ENTERPRISE (MSME) DEVELOPMENT STRATEGY IN ISLAMIC ECONOMIC PERSPECTIVE TO IMPROVE THE WELFARE OF STREET VENDORS (CASE STUDY OF STREET VENDORS IN MERLUNG VILLAGE, MERLUNG DISTRICT, TANJUNG JABUNG BARAT REGENCY) - Zuhratul Aulia; Sugiharto; Sumartini (INTERNATIONAL JOURNAL OF ECONOMIC LITERATURE, 2024)
UMKM make a sizeable contribution to the country's economic development. In Indonesia, one type of business that is developing in society is UMKM, which is a business activity engaged in various specific business fields. Because of its rapid development and its contribution to the welfare of society. In Merlung District, UMKM play an important role in reducing unemployment because the existence of UMKM can open up great job opportunities thereby increasing the welfare of the people. One of the UMKM that is often run by the community is Livelihood Activities which are small and medium enterprises that are used to make a living, for example, such as street vendors.